Inactivation of Matrix-bound Matrix Metalloproteinases by Cross-linking Agents in Acid-etched Dentin - Scheffel, D. L. S.; Hebling, J. [UNESP]; Scheffel, R. H.; Agee, K.; Turco, G.; Souza Costa, C. A. de; Pashley, D. (Operative Dentistry Inc, 2014)
Objectives: Published transmission electron microscopy analysis of in vitro resin-dentin bonds shows that, after 44 months, almost 70% of collagen fibrils from the hybrid layer disappear. Matrix metalloproteinases (MMPs) play an important role in that process and are thought to be the main factor responsible for the solubilization of dentin collagen. Therefore, this study aimed to evaluate the inactivation of matrix-bound MMPs by two different cross-linking agents, carbodiimide (EDC) or proanthocyanidin (PA), or the MMP-inhibitor, chlorhexidine (CHX), on acid-etched dentin using a simplified MMP assay method.Materials and Methods: Dentin beams (2x1x6 mm) were obtained from mid-coronal dentin of sound third molars and randomly divided into six groups (G) according to the dentin treatment: G1: Deionized water (control); G2: 0.1 M EDC; G3: 0.5 M EDC; G4: 0.5 M EDC + 35% hydroxyethyl methacrylate (HEMA); G5: 5% PA; and G6: 2% CHX. The beams were etched for 15 seconds with 37% phosphoric acid, rinsed, and then immersed for 60 seconds in one of the treatment solutions. The data were expressed both in absorbance values at 412 nm and in MMP-9 activity equivalents. The total MMP activity of dentin was analyzed for one hour by colorimetric assay (Sensolyte). Data were submitted to Wilcoxon nonparametric test and Mann-Whitney tests (p>0.05).Results: All experimental cross-linking solutions significantly reduced MMP activity from 79.8% to 95.2% when compared to the control group. No difference was observed among 0.1 M EDC (84.8%), 5% PA (87.6%), and 2% CHX (79.8%). Addition of 35% HEMA to 0.5 M EDC produced inactivation (95.2%) that was similar to that of 0.5 M EDC alone (92.7%).Conclusion: Dentin treatment with cross-linking agents is effective to significantly reduce MMP activity. Mixing 0.5 M EDC and 35% HEMA did not influence EDC inhibitor potential.